Delta CHA2DS2-VASc score as a predictor of stroke - El-Battrawy, Ibrahim; Borggrefe, Martin; Lang, Siegfried; Zhou, Xiao-Bo; Akın, Ibrahim (Europace, 2019)
The article by Uittenbogaart et al.1 published in Europace describing the relationship between atrial fibrillation (AF) burden and risk of stroke elucidated gre
Published: 09 May 2018
Gesehen am 25.06.2019
Ziffer 2 ist im Titel tiefgestellt